(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2016)
Brushless DC (BLDC) Motors are receiving significant attention from industries since the last decade. They are extremely reliable and weightless than other machines of comparable power outputs; also they are suitable for high speed applications such as in CNC milling machines. Although the design procedures of the machine are available as a concatenation of many different sources, the need for an unified, step-by-step design procedure from first principles of electromagnetic is an absolute requirement. The objective of this project is to design an Internal Permanent Magnet Brushless DC (IPMBLDC) Motor. Once it was determined what type and size of material available for stator and rotor, a reasonable size and power output estimated. Using general radial flux concept the design was refined. Software tool, RMxprt of ANSYS is used to build geometry of motor and to calculate basic design parameters, and then this design is taken into Maxwell 2D environment to further analyze it.